2007
DOI: 10.1007/s11259-007-3566-7
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study to Assess the Feasibility of a Submaximal Exercise Test to Measure Individual Response to Cardiac Medication in Dogs with Acquired Heart Failure

Abstract: Exercise testing is not commonly used in canine medicine because of several limitations. The aim of this study was to investigate the suitability of a treadmill test to measure the exercise capacity of untrained canine cardiac patients and to measure some biological parameters that might reflect the tolerance of dogs with heart failure to submaximal exercise. The exercise capacity of seven dogs with naturally occurring heart failure was evaluated before the institution of cardiac medication and 7 days after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…This possible positive influence of administering pimobendan was only observed at day 180, however. Ferasin et al observed a coincided decrease in plasma lactate concentration with better exercise tolerance of dogs with acquired heart failure (New York Heart Association (NYHA) classes 2 and 3) [26]. Thus, a lower increase during exercise and lower level of lactate after exercise might indicate a better exercise tolerance and thus a better life-quality of the dogs treated with pimobendan.…”
Section: Discussionmentioning
confidence: 99%
“…This possible positive influence of administering pimobendan was only observed at day 180, however. Ferasin et al observed a coincided decrease in plasma lactate concentration with better exercise tolerance of dogs with acquired heart failure (New York Heart Association (NYHA) classes 2 and 3) [26]. Thus, a lower increase during exercise and lower level of lactate after exercise might indicate a better exercise tolerance and thus a better life-quality of the dogs treated with pimobendan.…”
Section: Discussionmentioning
confidence: 99%
“…Significant mild increases of cTnI have already been reported in healthy dogs after sled races [ 31 33 ], where workload was a lot higher than in the submaximal exercise protocol. A slightly increased exercise cTnI was found in dogs with heart failure (CHIEF C) that underwent submaximal ET [ 34 ]. While samples were drawn 3 h post exercise in the present study, Ferasin et al (2007) measured cTnI immediately after exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Because cTnI has been reported to reach peak serum levels hours after a cardiac event [ 34 , 39 ], it was measured before and 3 hours after the ET. Samples for cTnI and NT-proBNP were stored on ice within seconds after extraction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…the evaluation of these variations it is of the utmost importance to understand which metabolic pathways are involved, and which physiological adaptations are induced by different types of exercise [1]. But although it is important to understand all modifications because they reflect changes in the functions of different systems and in the type of energy utilized [13], few authors have studied the responses during a specific aerobic test [2,5,22]. recently, the effect of a treadmill exercise program on plasma cortisol hormone level and some physiological and hematological parameters have been evaluated in German shepherd dogs [16,17].…”
Section: Introductionmentioning
confidence: 99%